Male X-linked genes in Drosophila melanogaster are compensated independently of the Male-Specific Lethal complex. - Philip, P.; Stenberg, P. (Epigenetics & chromatin, 2013)
In organisms where the two sexes have unequal numbers of X-chromosomes, the expression of X-linked genes needs to be balanced not only between the two sexes, but also between X and the autosomes. In Drosophila melanogaster, the Male-Specific Lethal (MSL) complex is believed to produce a 2-fold increase in expression of genes on the male X, thus restoring this balance.Here we show that almost all the genes on the male X are effectively compensated. However, many genes are compensated without any significant recruitment of the MSL-complex. These genes are very weakly, if at all, affected by mutations or RNAi against MSL-complex components. In addition, even the genes that are strongly bound by MSL rely on mechanisms other than the MSL-complex for proper compensation. We find that long, non-ubiquitously expressed genes tend to rely less on the MSL-complex for their compensation and genes that in addition are far from High Affinity Sites tend to not bind the complex at all or very weakly.We conclude that most of the compensation of X-linked genes is produced by an MSL-independent mechanism. Similar to the case of the MSL-mediated compensation we do not yet know the mechanism behind the MSL-independent compensation that appears to act preferentially on long genes. Even if we observe similarities, it remains to be seen if the mechanism is related to the buffering that is observed in autosomal aneuploidies.